Nitrogen Sources in Young Peach Trees in the Presence and Absence of Paspalum notatum Co-Cultivation - Paula, Betania Vahl de; Rozane, Danilo Eduardo [UNESP]; Santos, Eduardo Maciel Haitzmann dos [UNESP]; Vitto, Beatriz Baticini; Hindersmann, Jacson; Antunes, Luis Eduardo Correa; Nava, Gilberto; Loss, Arcângelo; Melo, George Wellington Bastos de; Nicoloso, Fernando Teixeira; Brunetto, Gustavo (MDPI, 2022)
Nitrogen (N) sources are applied to soils cultivated with peach trees. But, soil cover crops, as Paspalum notatum, a Pampa biome native species, commonly present in orchards, can absorb part of N, decreasing the amount used by peach trees. The study aimed to evaluate N absorption and physiological parameters of young peach trees cultivated in soil with the presence and absence of Paspalum notatum. The experiment was carried out for 180 days in a greenhouse, where N sources were applied to peach trees in the presence or absence of Paspalum notatum. Urea and organic compost were used. Dry matter, tissue N and physiological parameters were evaluated in peach trees. Dry matter and tissue N were evaluated in Paspalum notatum. Nitrogen in soil was evaluated. The N uptake by the peach trees with urea application, on average, was 32% higher than the N uptake by the peach trees in the control treatment or with organic compost, regardless of the presence or absence of Paspalum notatum. Cultivation with Paspalum notatum decreased N uptake by peach trees and, consequently, peach trees photosynthetic pigment content, and stimulated senescence anticipation in about 30 days. However, the total dry matter of peach trees cultivated with Paspalum notatum in any of the treatments applied was not modified. These results may guide new ways of co-cultivating cover crops and young peach trees.
Keywords: cover crops; mineral source; organic source; Prunus persicaL